Implementasi Model Pembelajaran Gal’perin untuk Meningkatkan Aktivitas dan Kemampuan Berfikir Kritis Mahasiswa pada Pembelajaran Statistika - Soenarko, Bambang; Hunaifi, Abdul Aziz; Aka, Kukuh Andri (Universitas Nusantara PGRI Kediri, 2020)
This research is a classroom action research study of the Gal'Perin model implementation process, the results of performance improvement and critical thinking skills (CBC) of students. Based on classroom action research for 2 cycles, it was found that the implementation of learning by the model lecturers using the Gal'Perin model had been 100% successful. Active students show scores above ≥ 75% and can be given active students. The average score of students' learning activeness from cycle I always shows improvement compared to previous meetings. Cycle I scores reach 72 and Cycle II reaches 79. The average CBC as a form of student learning outcomes classically in cycle 1 consists of 79 and in cycle 2 amounts to 82, thereby increasing the increase that does not show a significant difference what is evident from paired tests t-test with Sig. (2-tailed) of 0.149, which means greater than 0.05, then conclusions can be drawn that are not significantly different between the results of KBK cycle 1 and cycle 2.